Motivational Aspects Of United Nations Volunteers In Pakistan - Shah, Tariq (2023)
United Nations Volunteers (UNVs) play a crucial role in development and peacebuilding across the globe. Their role has become more pivotal in a country like Pakistan, configured with dismal socio-economic development and confronted with many natural disasters like earthquakes, and man-made calamities like conflicts, wars, and law and order situations. The present study looked into the motivating and hygiene factors by referring to the Herzberg two-factor theory. Understanding UNVs' motivation and their challenges requires the researcher to interact with them in their actual working contexts. Therefore, the qualitative research method remained the most appropriate to attain relevant and deeper insights into motivating factors and the challenges the UNVs confronted. This research employed an interpretive paradigm to